Sao Tome and Principe : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues Paper and Statistical Appendix presents a summary of the tax system as of December 1995 of Sao Tome and Principe. It describes the exchange and payments system. The paper highlights that the currency of Sao Tome and Principe is the Sao Tome and Principe dobra. The official exchange rate is determined daily as an average of exchange rates in the bureau de change, parallel market, and a commercial bank. Foreign exchange transactions are divided into three categories, namely import payments, transactions in foreign checks, and collection of export proceeds.